R&D, Scope Economies and Company Structure: A "Not-so-Fixed Effect" Model of Plant Performance - Tor Jakob Klette (Statistics Norway, Research Department, 1994)
Some well-known correlations between R&D and performance are given a somewhat new interpretation in this paper. I present an alternative model of knowledge accumulation, with some interesting and desirable properties. Perhaps the most attractive property is that it provides a simple and less data intensive framework for empirical studies of the relationship between firm performance and R&D. This property allows me to address some new aspects of this relationship combining two rich, new sources of firm and plant-level data. Among the substantial empirical findings are (i) R&D has a positive and significant effect on performance, (ii) the estimates suggest that the appropriable part of knowledge capital depreciate at a rate of 0.2, (iii) there are visible spillover effects of R&D across LBs within a firm (economies of scope in R&D), and (iv) there are significant spillovers in R&D across firms that belong to the same interlocking group of firms.
Keywords: D24; O30; 330; Productivity; R&D; Corporate structure; Microeconometrics.